A sequence motif enriched in regions bound by the Drosophila dosage compensation complex. - Gallach, M.; Arnau, V.; Aldecoa, R.; Marín, I. (BMC Genomics, 2010)
In Drosophila melanogaster, dosage compensation is mediated by the action of the dosage compensation complex (DCC). How the DCC recognizes the fly X chromosome is still poorly understood. Characteristic sequence signatures at all DCC binding sites have not hitherto been found.In this study, we compare the known binding sites of the DCC with oligonucleotide profiles that measure the specificity of the sequences of the D. melanogaster X chromosome. We show that the X chromosome regions bound by the DCC are enriched for a particular type of short, repetitive sequences. Their distribution suggests that these sequences contribute to chromosome recognition, the generation of DCC binding sites and/or the local spreading of the complex. Comparative data indicate that the same sequences may be involved in dosage compensation in other Drosophila species.These results offer an explanation for the wild-type binding of the DCC along the Drosophila X chromosome, contribute to delineate the forces leading to the establishment of dosage compensation and suggest new experimental approaches to understand the precise biochemical features of the dosage compensation system.